The Impact Of Leadership, Training, And Work Commitment On Work Productivity Through Employee Career Development - Kustini Kustini; Denok Sunarsi; Imas Masriah (International Journal of Social Sciences, 2026)
This research aims to analyze the influence of leadership, training, and work commitment on employee work productivity through career development. The research approach employs a quantitative method with Structural Equation Modeling–Partial Least Squares (SEM-PLS) analysis. The sample consists of 187 permanent employees. The results indicate that leadership, training, and work commitment have a significant positive effect on career development and work productivity. Career development also mediates the relationship between the independent variables and productivity. The R² values ​​show that the model explains 90.7% of the variation in career development and 93.8% of the variation in productivity.